Spider-Ham. A pig in time : an original graphic novel - Foxe, Steve (Graphix chapters., 2024)
To stop the future Green Gobbler from teaming up with his present-day counterpart and save New Yolk City, Spider-Ham joins forces with heroes from across time to foil the duo's dastardly plan.